Membangun Pola Pengasuhan Aman dan Inklusif Bagi Anak Disabilitas - Fathul Isya Aiyuning (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This article aims to describe the forms of danger, identify the causal factors, formulate strategies, and explain the role of parents in creating safe and inclusive parenting for children with disabilities. Children with disabilities are highly vulnerable to various forms of danger, including physical and emotional neglect, due to a lack of parental understanding and strong social stigma. The method used is descriptive qualitative with a literature review approach, analyzing data from books, scientific journals, and official reports. The results indicate that risky parenting is caused by a lack of knowledge, economic pressure, and insufficient support from the environment and Non-Formal Education (NFE) institutions. The key strategy to overcome this is through strengthening parental education (inclusive parenting classes), collaboration between NFE institutions and the community, and creating accessible and secure learning environments. In conclusion, NFE has a strategic role as a bridge for parents to gain knowledge and support, thus strengthening a safe, loving, and difference-appreciating family environment. This research emphasizes the novelty of NFE’s role in integrated family-community support to ensure optimal development for children with disabilities.